UJI PERFORMANSI CUTTING FLUID PADA PROSES PEMESINAN DRILLING PLAT BAJA - Bobby Kharisma; Rusnaldy Rusnaldy (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2015)
Cutting fluid is a very important component in the process of machining (metal-cutting operation), in addition to extend tool life cutting fluid in some cases able to reduce cutting force and refine the product surface machining results.Machining conditions used in this study are machined dry (do not use cutting fluid) and by using cutting fluid dromus and synthetic oil. Workpiece material used as test specimens in this reserches is a steel JIS G3106 SM490YA. And for material of cutting tool used is made of High Speed Steel (HSS).To know the performance of the cutting fluid can be known from measurements such as tool wear generated. Tool wear measurement is done by use spindle speed 2500 rpm and perform ingestion 150 times for each tools and variable. Also, provide load 150 kg on drilling machine handle. From the testing will be known cutting fluid which has the best performance. Good performancecutting fluid is can decrease the friction between the cutting tool with the workpiece so that hasthe smallest tool wear generated so that it can extend cutting tool lifeCutting fluid is a very important component in the process of machining (metal-cutting operation), in addition to extend tool life cutting fluid in some cases able to reduce cutting force and refine the product surface machining results.Machining conditions used in this study are machined dry (do not use cutting fluid) and by using cutting fluid dromus and synthetic oil. Workpiece material used as test specimens in this reserches is a steel JIS G3106 SM490YA. And for material of cutting tool used is made of High Speed Steel (HSS).To know the performance of the cutting fluid can be known from measurements such as tool wear generated. Tool wear measurement is done by use spindle speed 2500 rpm and perform ingestion 150 times for each tools and variable. Also, provide load 150 kg on drilling machine handle. From the testing will be known cutting fluid which has the best performance. Good performancecutting fluid is can decrease the friction between the cutting tool with the workpiece so that hasthe smallest tool wear generated so that it can extend cutting tool life.